Vitamins and Mineral composition of Sorghum vulgare leaf-sheath, Eremomastax polysperma and Brillantaisia owariensis - Akuru, Gift (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2018)
This study estimated the vitamins and minerals content present in Sorghum vulgare leaf-sheath, Eremomastax polysperma and Brillantaisia owariensis leaves.  The vitamin content was analysed using spectrophotometric method while minerals was determined, using atomic absorption spectrophotometric method. The vitamin C, vitamin E and vitamin D contents of Brillantaisia owariensis (59.961mg/100g; 10.370mg/100g; 20.254mg/100g) was higher than Sorghum vulgare leaf-sheath (52.975mg/100g; 10.188mg/100g; 14.400mg/100g) and Eremomastax polysperma (54.89mg/100g; 10.224mg/100g; 1.584mg/100g) respectively. Vitamin A concentration of Eremomastax polysperma (1.074mg/100g) was higher than Brillantaisia owariensis (0.224mg/100g) and Sorghum vulgare leaf-sheath (0.85mg/100g); while Sorghum vulgare leaf-sheath had a vitamin B6 concentration (222.50mg/100g) that was higher than Brillantaisia owariensis (120.00mg/100g) and Eremomastax polysperma (90.00mg/100g) leaves. The mineral contents showed the concentration of iron to be highest in all the plants; 32.317 µg/g in Sorghum vulgare leaf sheath, 35.202 µg/g in Brillantaisia owariensis, and 29.258 µg/g in Eremomastax polysperma. The manganese concentration of Brillantaisia owariensis (5.860 µg/g) was higher than Sorghum vulgare (5.547 µg/g) and Eremomastax polysperma (0.067 µg/g).  The results obtained suggests that  Sorghum vulgare leaf-sheath, Eremomastax polysperma and Brillantaisia owariensis leaves have appreciable amount of vitamins and minerals, which could aid in the general well-being of humans.